1991
DOI: 10.1037/0021-9010.76.3.432
|View full text |Cite
|
Sign up to set email alerts
|

A new meta-analytic approach.

Abstract: A new meta-analytic approach for assessing the generalizability of correlations or criterion-related validities is presented. The new approach incorporates specific procedures for estimating the sampling variance of corrected and uncorrected correlations. A major advantage of the new approach is the ease with which studies without any sample-based artifact data, with partial samplebased artifact data, or complete sample-based artifact data can be incorporated together into a practical procedure for meta-analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
174
0
4

Year Published

1993
1993
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(179 citation statements)
references
References 46 publications
1
174
0
4
Order By: Relevance
“…We conducted the analyses using the Raju, Burke, Normand, and Langlois (1991) approach to meta-analysis with an adapted version of Arthur, Bennett, and Huffcutt (2001) SAS PROC MEANS. In the Raju et al method, each effect size is individually weighted by the sample size and corrected for attenuation due to predictor and criterion unreliability.…”
Section: Analysesmentioning
confidence: 99%
“…We conducted the analyses using the Raju, Burke, Normand, and Langlois (1991) approach to meta-analysis with an adapted version of Arthur, Bennett, and Huffcutt (2001) SAS PROC MEANS. In the Raju et al method, each effect size is individually weighted by the sample size and corrected for attenuation due to predictor and criterion unreliability.…”
Section: Analysesmentioning
confidence: 99%
“…Not all of the studies reported information on the reliability of job satisfaction scales. When no information about reliability was reported, we estimated the reliability using the approach implemented in the meta-analytic procedure of Raju et al (1991). In other words, the approach of Raju et al allows for correction of test±retest correlations for unreliability in the job satisfaction measure (at both measurement periods) by taking sampling error in the sample-based reliability estimates into account.…”
Section: Calculationsmentioning
confidence: 99%
“…Typically, effect sizes are summarized by computing a weighted average of the effects found in primary studies, where the weights are the sample sizes of each study (Hedges & Olkin, 1985;Raju et al, 1991;Schmidt & Hunter, 2014) or within-study variance, which is itself an inverse function of sample size (Borenstein et al, 2009). Summary effect size estimates are usually accompanied by a confidence interval, which is derived from the standard error of the effect and thus captures the precision of the estimate (Borenstein et al, 2009;Raju et al, 1991;Schmidt & Hunter, 2014). All else being equal, the confidence interval around an effect size estimate decreases as the combined sample sizes of the primary studies increase.…”
mentioning
confidence: 99%